Internet- en Internet of Things-vaardigheden in Nederland anno 2021 - van Deursen, Alexander (Universiteit Twente, 2021)
This report provides an overview of the Internet and Internet of Things skills of the adult Dutch population. The purpose of this report is to outline the state of affairs in 2021. An impression is given of which skills are mastered at which level and which indicators play a role. Such a situation sketch serves as input for the following steps in developing effective policy: Explain why certain skills are mastered at a certain level and why certain indicators play a role.